(untitled) (Zaporizhzhia Historical Review, 2021)
The article is devoted to the educational institutions’ development for the occupied population of the South of Ukraine during the German-Romanian authority. The author considers educational system folksdoiche (Volks Deutsche) for ethnic Germans, which had common traits with German educational system.